A Technique for Arthroscopic Double-Row Rotator Cuff Repair With Acellular Dermal Matrix Augmentation - Chloe Xiaoyun Chan, M.B.B.S., M.R.C.S., M.Med. (Ortho.); Joshua Ian Lim, M.B.B.S.; Sean Wei Loong Ho, M.B.B.S., MRCS, M.Med. (Ortho.), F.R.C.S.Ed. (Ortho.); Luke Peter, M.B.B.S., B.Med.Sci., M.R.C.S., M.Med. (Ortho.), F.R.C.S.Ed. (Ortho.); Kevin Jing Hui Yik, M.B.B.S., M.R.C.S., M.Med. (Ortho.), F.R.C.S.Ed. (Ortho.) (Arthroscopy Techniques)
The outcomes of arthroscopic repair of large-to-massive rotator cuff tears remain suboptimal, with high retear rates reported. To overcome factors such as poor cuff quality and degenerate tendons with poor blood supply, augmentation with acellular dermal matrix allograft has emerged as a useful adjuvant procedure to promote healing. However, it remains a technically demanding procedure with a steep learning curve. Various described techniques require the use of additional suture anchors, tissue staples, or special instruments. This Technical Note describes a modified technique that streamline the steps and uses the standard 4 suture anchors for double-row cuff repair for the augmentation procedure.